Mixed-methods approach to studying multiuser perceptions of an interim Complete Streets project in Norway. (October 2022) - Vasilev, Miroslav; Pritchard, Ray; Jonsson, Thomas
Highlights: Implementing road diets as trial projects is beneficial for the planning process. The use of a PPGIS tool helped in the identification of several perceived safety issues. Users' preferences for bicycle solutions do not vary substantially among different user types. Two-way bicycle paths were perceived as unsafe at intersections. Abstract: Research on multiuser perceptions of street environment alterations has been gathering attention in recent years given an increased focus on both sustainable city development and public participation. This study investigated the value of applying a mixed-methods approach to investigating user perceptions of Complete Streets projects. It employed an online survey of 719 users of a case study street in Trondheim, Norway which received an interim infrastructural treatment including a road diet and a separated bicycle path. The survey presented the respondents with manipulated photographs showing the implemented interim design solution and six different potential streetscape configurations in order to explore their street design preferences. Additionally, the use of an integrated mapping application programming interface (API) allowed the participants to place markers with comments along the project map to explain where and why they had felt unsafe in relation to their use of the street before and after the implementation of the interim street modification, although both were collected in the after period. The ability of users' demographic characteristics and transport behavior to explain variations in perceptions and preferences was explored. It was confirmed that the participants favored separated bicycle path designs and that their preferences did not vary considerably among the different user types. The analysis of the distribution of the unsafe points from both time periods helped in the identification of traffic safety issues that might not have been uncovered if only stated preference methodologies were used. Additionally, it was shown that implementing such street alternations as interim projects could be beneficial for the planning process by providing the planners with insights on the way changes to the street environment would be experienced by the users.